2019
DOI: 10.1016/j.sjbs.2019.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Determination of metals as bio indicators in some selected bee pollen samples from Jordan

Abstract: This study was done to determine the degree of metals and heavy metals in some bee pollen sample as biological indicator for environmental pollution. Sample were collected from industrial, urban and agricultural areas of Jordan in year 2017. Eight metals (As, Cd, Cu, Mg, Pb, Ni, Se, and Zn) continents analyzed by using Inductively Coupled Plasma Optical Emission Spectrum, (ICP-OES).Results were statistically interpreted by using ANOVA analysis. Metals content in bee pollen from Jordan and China were determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 12 publications
3
25
0
Order By: Relevance
“…Minerals are permanent constituents of pollen, and elements such as K, Ca, P, Mg, Zn, Fe, Mn, Cu, Na and Cr, are frequently reported [ 53 , 54 , 55 ]. Some research in Serbia [ 53 ] and Turkey [ 54 ] revealed that the most abundant elements in pollen are K, P, Ca, and Mg; see Table 7 .…”
Section: Resultsmentioning
confidence: 99%
“…Minerals are permanent constituents of pollen, and elements such as K, Ca, P, Mg, Zn, Fe, Mn, Cu, Na and Cr, are frequently reported [ 53 , 54 , 55 ]. Some research in Serbia [ 53 ] and Turkey [ 54 ] revealed that the most abundant elements in pollen are K, P, Ca, and Mg; see Table 7 .…”
Section: Resultsmentioning
confidence: 99%
“…In that sense, [11] reported that seven floral maize pollen samples contained between 69 and 176 µg/kg of selenium. Three bee-collected pollen samples from Jordan had even more selenium: 1752-3030 µg/kg [148].…”
Section: Pollen As a Source Of Seleniummentioning
confidence: 99%
“…Samples from MAEPS had exceeded the acceptable limit of Pb in bee pollen (0.5 mg/kg) set by Campos et al [33] but have Pb content less than the Pb limit set by the Malaysian Food Regulation, 1985 (2 mg/kg). High Pb content was also reported in bee pollen from the industrial part of Jordan, with the value of 2.567 mg/kg [74]. However, Roman [69] detected a higher Pb content in a bee pollen sample from the Poland agricultural region with the value of 3.900 mg/kg.…”
Section: Heavy Metalmentioning
confidence: 99%
“…e increase of anthropogenic activities such as pesticide usage, land use, and industrial activities has led to the increase of heavy metal pollution in the environment. ese activities are different based on the geographical landscapes such as urban, agricultural, and industrial areas, which eventually lead to different levels of heavy metal pollution in the pollen [69,74]. However, pollen's ability to bioaccumulate heavy metals has created an opportunity for the pollen to become a bioindicator to detect heavy metal pollution in the environment.…”
Section: Heavy Metalmentioning
confidence: 99%